Control Strategy for Three-Phase Current-Source Inverters Based on Lyapunov's Direct Method - Komurcugil, Hasan; Kukrer, Osman (IEEE, 2008)
A new control strategy for three-phase current-source inverters is proposed based on a model of the converter in the rotating dq frame. The control equations are derived by making use of Lyapunov's direct method. It is shown analytically that a globally stable operation is possible for the closed-loop system. The amplitude of the dc current is adjusted by employing a proportional-integral regulator in the output voltage control loop. The correct operation of the proposed strategy is verified through simulations. Results pertinent to a step load change indicate that reasonably fast responses of the output voltage without large distortion can be obtained.
IEEE International Symposium on Industrial Electronics -- JUN 30-JUL 02, 2008 -- Cambridge, ENGLAND
Keywords: Drive System